Book review: Findlay, G. H; Dr. Robert Broom, F. R. S. Palaeontologist and physician/1866-1951. A biography, appreciation and bibliography. - Haughton, S. H. (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 1973)
This book, of 208 pages and 57 illustrations, is priced at R7,50.